Postpartum psychosis, infanticide and the law - Maier-Katkin, Daniel (Crime, law and social change, 1991)
In the past few years postpartum phychosis has been offered as a legal defense in a small number of deeply disturbing infanticide cases in several American jurisdictions. These cases have attracted a great deal of media attention, and fueled public discussion about the mental health of mothers who kill their own babies. From the perspective of the criminologist these cases present an extraordinary pattern of criminal behavior. Not merely a few isolated incidents, but a recurring pattern of the destruction of planned-for, wanted children by their own mothers with no apparent motive and under circumstances that suggest transitory postpartum phychoses. This article presents a detailed examination of specific cases aimed at exploration of the following issues: Are these women insane at the time of the act? Is their behavior the product of a diseased state of mind, or is it premeditated and willful? These issues lie at the core of the concept of criminal responsibility.